From Connectivity to Advanced Internet Services: A Comprehensive Review of Small Satellites Communications and Networks. (2nd May 2019) - Burleigh, Scott C.; De Cola, Tomaso; Morosi, Simone; Jayousi, Sara; Cianca, Ernestina; Fuchs, Christian
Abstract : Recently, the availability of innovative and affordable COTS (Commercial Off-The-Shelf) technological solutions and the ever-improving results of microelectronics and microsystems technologies have enabled the design of ever smaller yet ever more powerful satellites. The emergence of very capable small satellites heralds an era of new opportunities in the commercial space market. Initially applied only to scientific missions, Earth observation and remote sensing, small satellites are now being deployed to support telecommunications services. This review paper examines the operational features of small satellites that contribute to their success. An overview of recent advances and development trends in the field of small satellites is provided, with a special focus on telecommunication aspects such as the use of higher frequency bands, optical communications, new protocols, and advanced architectures.